Managing business conflict: the use of "alternative dispute resolution" in business disputes - Stipanowich, Thomas J. (Henry Stewart Talks, 2013)
Crisis in U.S. litigation, Vanishing trial, Reasons for reduction in trial, E-discovery concerns, Cuts in court funding, Need for tailored approaches to conflict resolution, Landmark survey of corporate counsel, Policies of Fortune 1,000 companies, Reasons companies using ADR (alternative dispute resolution), Corporate experience with various forms of ADR, Mediation, Frequency of use of mediation for different kinds of disputes, Mediation vs. arbitration, Frequency of use of arbitration for different kinds of disputes, Commercial mediation and arbitration, Employment mediation and arbitration, Consumer mediation and arbitration, Likelihood of future corporate use of mediation and arbitration, Lessons from recent survey, Potential benefits of mediation, Earlier studies of results, satisfaction with mediation, Estimated savings with mediation, Mediation outcomes in cases involving relationships, Recent growth areas for mediation, Mediation of intellectual property disputes, Mediation of international commercial disputes, Myths about mediation, Trends in mediation, Mediator as case manager, Reasons businesses use arbitration, Trends in arbitration, International arbitration -Arbitration as a choice-based process, Problems with companies not exercising choice options in arbitration, Reasons companies do not use arbitration, Addressing concerns about arbitration awards, Concerns about lack of appeal in arbitration, Appellate arbitration, Contractually expanded judicial review of arbitration awards, Concerns about arbitrator compromise, Concerns about costs and delays in arbitration, Share responsibility for costs and delays in arbitration, Protocols for expeditious, cost-effective commercial arbitration, Expanded use of arbitration in employment and consumer cases, Public policy limits on arbitration, Preemption of state law by federal arbitration law, Unconscionability as a policing tool for courts, Arbitrability issues, Recent Supreme Court decisions, Rent-A-Center, West v. Jackson, AT&T Mobility v. Concepcion, class action waivers and arbitration agreements, Congressional responses to Supreme Court decisions on arbitration, Multi-step dispute resolution processes, Hybrid processes (med-arb), Early Case Assessment, Real-time approaches to conflict in business relationships, Workplace conflict resolution systems, Early neutral evaluation, Evolving dispute resolution roles for lawyers, Impact of online dispute resolution and information technology, Keys to effective conflict management, Changing approaches for businesses and counsel, Conflict management checklist